Oral vinorelbine and continuous low doses of cyclophosphamide in pediatric rhabdomyosarcoma: a real-world study - Lan, Yingxia; Wu, Liuhong; Hong, Ye; Sun, Xiaofei; Wang, Juan; Huang, Junting; Sun, Feifei; Zhu, Jia; Zhen, Zijun; Zhang, Yizhuo; Song, Mengjia; Lu, Suying (Frontiers in Pharmacology, 2023)
Metronomic maintenance therapy (MMT) has significantly improved the survival of patients with high-risk rhabdomyosarcoma in clinical trials. However, there remains a lack of relevant data on its effectiveness in real-world situations. We retrospectively retrieved data of 459 patients ˂ 18 years of age diagnosed with rhabdomyosarcoma at Sun Yat-sen University Cancer Center from January 2011 to July 2020 from our database. The MMT regimen was oral vinorelbine 25-40 mg/m² for twelve 4-week cycles on days 1, 8, and 15, and oral cyclophosphamide 25-50 mg/m² daily for 48 consecutive weeks. A total of 57 patients who underwent MMT were included in the analysis. The median follow-up time was 27.8 (range: 2.9 - 117.5) months. From MMT to the end of follow-up, the 3-year PFS and OS rates were 40.6 ± 6.8% and 58.3 ± 7.2%, respectively. The 3-year PFS was 43.6 ± 11.3% in patients who were initially diagnosed as low- and intermediate-risk but relapsed after comprehensive treatment (20/57), compared with 27.8 ± 10.4% in high-risk patients (20/57) and 52.8 ± 13.3% in intermediate-risk patients who did not relapse (17/57). The corresponding 3-year OS for these three groups was 65.8 ± 11.4%, 50.1 ± 12.9%, and 55.6 ± 13.6%, respectively. We present a novel study of MMT with oral vinorelbine and continuous low doses of cyclophosphamide in real-world pediatric patients with RMS. Our findings showed that the MMT strategy significantly improved patient outcomes and may be an effective treatment for high-risk and relapsed patients.